Concepts of understanding the essence of the “abuse of rights” category (Law and Safety, 2023)
The research is devoted to defining the essence of the abuse of rights and highlighting the main concepts for understanding this category. It has been emphasized that in the legal literature the issue of the abuse of rights is considered ambiguously, and the publication authors have different opinions on this subject. There is a view that the very term “abuse of rights” is controversial. Approaches to understanding the essence of the category of “abuse of rights” are divided into two broad groups depending on the theory of right origin that is used to study this manifestation. Thus, supporters of the natural law theory consider the abuse of rights as a certain ethical minimum of a subject's behaviour, which allows him or her to commit certain actions for which he or she will not be held legally liable. Supporters of the positivist theory generally deny the existence of the category of “abuse of rights” because there is no clear definition of this concept at the regulatory level.It has been identified the main signs of abuse of rights. Therefore, it has been noted that abuse of rights balances on a fine line with an offense. It is enough to take a minor step, and in some cases the reflection of the act committed by the subject can be found in the relevant article of the Criminal Code, which turns legally neutral behaviour into an offense.Exploring the issues of approaches put forward by researchers to understanding the essence of the category “abuse of rights”, it is possible to distinguish the following concepts: abuse of rights does not exist; abuse of rights is socially harmful behavior which, however, does not violate the law; moral principle, performance of lawful behaviour; exercise of rights contrary to their purpose; types of abuse: those that are not characterized by obvious unlawfulness, which is expressed in the socially harmful behaviour of an authorized person who relies on a subjective right belonging to him/her; a type of legal nihilism; a special type of offense; a form of exercising a right contrary to its purpose, goal, social function or interests of other subjects.
Keywords: right; abuse of rights; philosophical understanding; concept; lawful behaviour; legal liability.